Unlocking Potential: Youth Contribution to Enhancing Community Empowerment through Labuhan Ageng at Sembukan Beach - Pradani, Eka Septi (UM Purwokerto Press, 2025)
The development of community empowerment in Indonesia has involved active participation from youth. This study focuses on Labuhan Ageng, analyzing the involvement of youth in contributing community empowerment activities organized by both the government and the youth. The research aims to comprehensively examine the forms of youth participation in the traditional ceremony namely Labuhan Ageng. Employing a descriptive qualitative approach, data for this research were gathered through interviews, observation, and documentation. Data were obtained through transcriptions of in-depth interviews with key informants, including the Traditional holder, the Village Head, and the residents of Paranggupito Village. Data analysis involved reduction, data display, and conclusion. The research findings indicate that collaborative strategies between youth and local government in traditional Labuhan Ageng ceremonies enhance community empowerment around Sembukan Beach. Collaboration through tourism ambassadors, youth-managed social media, and the participation of local youth in UNESCO activities helped introduce the tradition of Labuhan Ageng as one of the cultural treasures in Indonesia. As a result, the Labuhan Ageng tradition can attract both local and international tourists, increasing local revenue and significantly contributing to community empowerment.